The Development of Medical Skills Through Human Resources Management in Griya Sehat Shareeah, Depok City - Dona Suzana; Ditiya Himawati; Quroyzhin Kartika Rini; Dharmayanti (LPPM Universitas HKBP Nommensen, 2025)
In the era of globalization, traditional therapy clinics are required to ensure high personnel performance in providing services to the community, especially patients as the object of service. The low level of knowledge of health workers regarding health credential management affects the performance and quality of services in clinics. The aim of the health workers credential training activity is to improve the quality of health services at Griya Sehat Shareeah, Depok City. The community service activity was attended by 13 health workers from Griya Sehat Shareeah. Training is carried out with several practice sessions and an ongoing training program that focuses on technical and moral support efforts. The results of training show that there are differences in the level of knowledge after being given training to health workers. Thus, credential management training using lectures and practice methods can increase health workers knowledge about credential management and strengthen knowledge of the competence and authority of health workers at Griya Sehat Shareeah in providing health services so as to improve service quality. In the end, Griya Sehat Shareeah became an exemplary model that was able to combine traditional medicine with modern medicine in society.